Organic matter chemistry and bacterial community structure regulate decomposition processes in post-fire forest soils. (September 2021) - Ling, Lu; Fu, Yingyi; Jeewani, Peduruhewa H.; Tang, Caixian; Pan, Shaotong; Reid, Brian J.; Gunina, Anna; Li, Yongfu; Li, Yongchun; Cai, Yanjiang; Kuzyakov, Yakov; Li, Yong; et al.
Abstract: Wildfires decrease forest aboveground biomass and have long-term legacy effects on carbon (C) stocks in soil via alterations of microbial communities and functions. However, the interactions between soil organic C (SOC) chemodiversity and bacterial communities that drive C decomposition remain unclear. Soils from two boreal forest sites, 3 months (S1) and 15 years (S2) after fire events, were incubated for 53 days to quantify the mineralization of sucrose (mimicking rhizodeposits, δ13C = −11.97‰) and SOC priming. To reveal SOC-bacterial interactions that regulate SOC decomposition, the isotopic abundance, SOC chemical composition ( 13 C NMR), and associated bacterial community structure (16S rRNA gene sequencing) were analyzed. The best multivariate model (DISTLM) analysis indicated that aromatic C (phenolic-C and aryl-C) in S1 and di-O-alkyl C in S2 were the largest contributors to bacterial community structure. The co-occurrence network confirmed SOC-bacteria interactions, and revealed the highly co-occurrent groups, i.e. Paenibacillus in S1 and Bacillus in S2, both of which belong to the Firmicutes, correlated with recalcitrant C and labile C, respectively, and are potentially linked to decomposition. For example, Firmicutes (as well as Proteobacteria and Actinobacteria) were correlated with aryl-C and phenolic-C in S1 and highly correlated with SOC priming intensity. The limited C resources (enriched refractory components, i.e. phenolic substances) in S1 favored oligotrophs to outcompete other bacterial groups, which likely aided decomposition of more recalcitrant SOC via co-metabolisms. The slow decomposition of sucrose and large soil priming effects observed in S1 suggested a faster SOC turnover via bidirectional processes of additional sucrose-C gain and native soil-C loss. Collectively, changes in SOC chemistry were coupled with an altered bacterial community, and their interactions might further correlate to decomposition, with implications for C sequestration in the post-fire boreal forest soils. Graphical abstract: Image 1 Highlights: We investigated soil priming effects in post-fire forest soils. Soil microbial diversity decreased with soil depth. NMR and sequence analyses were utilized to understand C-microbe interactions. Positive association between aromatic-C and Firmicutes was correlated to SOC loss.